Abdominal obesity and incident cardio-metabolic disorders in Asian-Indians: A 10-years prospective cohort study. Issue 2 (February 2022) - Jayant, Satyam Singh; Gupta, Rahul; Rastogi, Ashu; Agrawal, Kanhaiya; Sachdeva, Naresh; Ram, Sant; Dutta, Pinaki; Bhadada, Sanjay Kumar; Bhansali, Anil
Abstract: Background and aims: To estimate the strength of association between abdominal obesity and incident cardio-metabolic diseases. Methods: A subset of Chandigarh Urban Diabetes study cohort (n = 543) was followed after a mean of 10.7 years for development of diabetes, prediabetes, dysglycaemia (either prediabetes or diabetes), hypertension and atherosclerotic cardiovascular disease (ASCVD). Diabetes and prediabetes were defined as per American Diabetes Association consulting group criteria, hypertension as blood pressure of ≥140/90 mmHg and ASCVD after review of medical records. Abdominal obesity was defined as waist circumference of ≥80 cm and ≥90 cm in females and males, respectively. Results: As compared to non-obese (n = 209), abdominally obese individuals (n = 334) had a higher risk of diabetes [RR:1.82(1.28–2.57)], prediabetes [RR:1.40(1.05–1.85)], dysglycaemia [ RR:1.38(1.07–1.78)], hypertension [RR: 1.84(1.30–2.59)] and ASCVD [RR:2.12(1.02–4.4)]. The optimal cut-off of waist circumference for detecting incident diabetes, hypertension and ASCVD in females was 88 cm, 85 cm and 91 cm, respectively; while in males it was 90 cm, 87 cm and 94 cm, respectively. Conclusion: In Asian-Indians, abdominal obesity as defined by waist circumference of ≥90 cm and ≥80 cm in males and females, respectively is associated with a twofold higher risk of diabetes, hypertension and ASCVD. In addition, the current-cut-offs of waist circumference to define abdominal obesity need reconsideration to optimally identify individuals at a higher risk of cardio-metabolic diseases. However, a high attrition rate represents a major limitation. Highlights: Study prospectively evaluated individuals with abdominal obesity for incidence of diabetes and hypertension over a decade. Centrally obese individuals have 1.95 and 2.19 times higher risk of diabetes and hypertension, respectively. The optimal waist circumference cut-off for predicting incident diabetes is 88 cm for female and 90 cm for male. Present waist circumference defining abdominal obesity need reconsideration to identify metabolic risk. Present study had attrition rate of 40% during follow up limiting the generalizability of findings.